![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
计算:(1)5×(-2)-90÷(-15);(2)?112+13+16;(3)(134?78?712)×(?87);(4)-14-(1-0.5)÷3
计算:(1)5×(-2)-90÷(-15);(2)?112+13+16;(3)(134?78?712)×(?87);(4)-14-(1-0.5)÷3×[3-(-3)2]....
计算:(1)5×(-2)-90÷(-15);(2)?112+13+16;(3)(134?78?712)×(?87);(4)-14-(1-0.5)÷3×[3-(-3)2].
展开
展开全部
(1)原式=-10+6=-4;
(2)原式=?1
+
=-1;
(3)原式=-2+1+
=?
;
(4)原式=-1-
×
×(3?9)=-1-(-1)=0.
(2)原式=?1
1 |
2 |
1 |
2 |
(3)原式=-2+1+
2 |
3 |
1 |
3 |
(4)原式=-1-
1 |
2 |
1 |
3 |
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询